Analytical Study of Medical Image Combination Techniques - Abbas, Heba Kh.; Mahdy, Anwar H.; Al Zuky, Ali A.; Ahmad, Sally F. (Iraqi Journal of Science, 2018)
Image combination is a technique that fuses two or more medical images taken with different conditions or imaging devices into a single image contain complete information. In this study relied on mathematical, statistical and spatial techniques, to fuse MRI images that captured horizontal and vertical times (T1, T2), and applied a method of supervised classification based on the minimum distance before and after combination process, then examine the quality of the resulting image based on the statistical standards resulting from the analysis of edge analysis, showing the results to identify the best techniques adopted in combination process, determine the exact details in each class and between classes.